Protein Isolate from Brown Seaweed, Sargassum tenerrimum: Extraction and Characterization - Behera, Sushri Subhasini 1; ELAVARASAN KRISHNAMOORTHY; MP, Safeena; Mathew, Suseela (Fishery Technology, 2023)
The demand for plant-based raw materials as a protein source is experiencing a notable increase, and within this context, seaweed has emerged as a promising and sustainable alternative. However, seaweed resources remain under-exploited in spite of their abundance along the Indian shores. In this study, an attempt was made to isolate protein from brown seaweed, Sargassum tenerrimum, using the pH shift-based technique. The seaweed protein isolate (SPI) contained 3.19 ± 0.84 % moisture, 51.13 ± 0.66 % protein, 2.55 ± 1.11 % fat, 18.07 ± 0.64 % ash and 25.06 ± 3.45 % total carbohydrate. The physicochemical and functional properties of seaweed protein isolate was also studied. From the results obtained, it is concluded that the locally available seaweed species such as S. tenerrimum could serve as a raw material for protein isolation. The protein isolate from S. tenerrimum can be used as an ingredient in protein-rich food formulations, including protein dietary supplements. However, it is necessary to make efforts towards improving the functional properties of the protein isolate to ensure its optimal suitability for a wide range of food applications.